A landscape scale assessment of domestic cat occurrence in boreal forests - Øyvind Skarsgard Nyheim; Asunción Semper‐Pascual; John Odden; Neri Horntvedt Thorsen; Richard Bischof (Conservation Science and Practice)
Abstract Domestic cats (Felis catus), both feral animals and pets, are a major threat to biodiversity. While domestic cats are closely associated with human residences and activity, they also range into and impact natural areas. We still know little about how free‐ranging cats use natural and semi‐natural areas. We quantified cat occurrence at 405 forest sites in Norway over 3 years using occupancy modeling, and tested how occurrence patterns were influenced by relevant landscape variables. Cat occupancy decreased with increasing distance from residential houses, being >60% within 50 m of the nearest house, but even at 1000 m distance, occupancy still exceeded 10%. When cats were present in forests, they were more likely to be detected close to forest edges. Detection probability was lowest and declined more steeply with increased distance from the forest edge during winter, when temperature, vegetation cover, and prey availability are at their lowest. We conclude that cats may pose a threat in natural areas like forests even at considerable distances from residences. We encourage further studies that investigate the role of landscape characteristics and environmental conditions on habitat penetration by both feral and pet domestic cats.